Ultrafast heating of metallic glasses reveals disordering of the amorphous structure. (1st February 2016) - Küchemann, Stefan; Samwer, Konrad
Abstract: Studies of the transition from the supercooled liquid into the high temperature liquid of a glass forming metal is commonly hindered by incipient crystallization processes. In this contribution we show that a metallic glass exhibits a significant sudden increase in the specific heat while crossing the transition from the supercooled liquid into the high temperature liquid without crystallizing. At this increase, high temporal resolution X-ray studies show that the liquid structure changes and the crystallization behavior also deviates from the common Zr2 (Cu, Al)-phase formation. We associate the increase in specific heat capacity with the disordering of the amorphous structure like a scenario of a first order liquid–liquid phase transition. Graphical abstract: